Karakteristik Remaja SMA dengan Faktor Risiko Diabetes Melitus di Kota Padang - Fauziah Qifti; Hema Malini; Hilda Yetti (Universitas Batanghari Jambi, 2020)
Diabetes mellitus is a non-communicable disease whose prevalence continues to increase every year. Adolescents are targeted in the selection and implementation of prevention of diabetes mellitus early on. This study aims to determine the characteristics of high school adolescents in the city of Padang who have risk factors for diabetes mellitus. This study is quantitative with cross sectional design. The sample of this study was high school students in Padang who met the inclusion criteria of 171 people. Of the total sample 48% were 16 years old, 33.3% were 17 years old, 16.4% were 15 years old and 0.6% were 19 years old. From the total sample, it is known that 64.3% are female and 35.7% male. Based on body mass index, it is known that 52.5% have a BMI ≥ 25 Kg / m² and 47.4% have a BMI <25 Kg / m². While the characteristics of students who have a family history of Diabetes Mellitus are 64.9% and do not have a family history of 35.1%. It is important for adolescents with risk factors to check blood sugar levels and get health education in order to increase awareness to take preventative measures early.